Association between FKBP5 polymorphisms and depressive disorders or suicidal behavior: A systematic review and meta-analysis study. (January 2019) - Hernández-Díaz, Yazmin; González-Castro, Thelma Beatriz; Tovilla-Zárate, Carlos Alfonso; Juárez-Rojop, Isela Esther; López-Narváez, María Lilia; Pérez-Hernández, Nonanzit; Rodríguez-Pérez, José Manuel; Genis-Mendoza, Alma Delia
Highlights: FKBP5 has attracted considerable attention as a new marker for depression and suicide. Genetic risk for depressive disorder was associated with the rs3800373 and rs4713916 polymorphisms. FKBP5 C > T (rs1360780) polymorphism may be a risk factor to develop a suicidal behavior. Abstract: Psychiatric disorders are complex polygenic diseases that show common genetic vulnerability. Several studies have investigated the association of polymorphisms of FK506 binding protein 51 (FKBP5) gene and depressive disorders or suicidal behavior, however, the results have been controversial and ambiguous. The aim of our study was to explore the role of the FKBP5 gene variants (rs1360780, rs3800373 and rs4713916), in depressive disorders or suicidal behavior through a systematic review and a meta-analysis. The protocol number of the study is PROSPERO CRD42018089295. The meta-analysis included 12 studies. Odds ratios with 95% confidence intervals were used to evaluate the association and the publication bias was tested by Egger's test and funnel plot; heterogeneity was assessed by the Cochran's chi-square-based Q statistic test and the inconsistency index. Our results showed that the rs3800373 and rs4713916 were associated with an increased risk of depressive disorders when using the heterozygous and dominant models. In the stratified analysis by ethnicity, a significantly increased risk of depressive disorders was also observed for rs3800373 and rs4713916 in Caucasians. When we analyzed suicidal behavior, we found a significant association with the rs1360780 of FKBP5 and suicidal behavior risk in the overall population and rs3800373 in completed suicide subgroup. Existing evidence indicates that the polymorphisms of FKBP5 gene are associated with risk of depressive disorders and suicidal behavior. Future studies with larger sample sizes will be necessary to confirm the present results.